Sparen in Zeiten niedriger Zinsen: Wirtschaftspolitische Unterstützung nötig? - Manuel Rupprecht; Christine Annuß (Wirtschaftsdienst, 2017)
Die Niedrigzinspolitik der EZB steht bei vielen deshalb in der Kritik, weil Sparer kaum Erträge durch ihre Anlagen erwirtschaften können. Tatsächlich bezieht sich diese Beobachtung aber vor allem auf die Entwicklung des nominalen Zinsatzes. Real ist die Gesamtrendite privater Haushalte in Deutschland derzeit nicht auf ihrem niedrigsten Stand. Allerdings sind die Portfolios privater Anleger in Deutschland wenig renditeorientiert. Die Autoren sind der Auffassung, dass die Politik hier ansetzen und weniger die direkte Subventionierung des Sparens in den Blick nehmen sollte. – – Critics of the low interest rate environment claim that German households have had difficult times generating positive returns from their savings since interest rates reached levels around zero. Therefore, direct public support is increasingly being called for. This article shows that, from a macroeconomic perspective, households have in fact generated positive real returns to date. However, portfolio returns may vary among households due to differences in portfolio structure and size. In addition, aggregate portfolio returns might decrease in the years to come if nominal interest rates remain low. Regarding policy responses, it is therefore proposed to undertake measures which increase total factor productivity and improve the financial literacy of households. Both approaches promise to be more effective than direct public support of savings.
Keywords: E21; G11; I22; 330